Effects of Distribution and the Formation Process of MA on Deformation and Toughness of High Strength Linepipe Steel - Tsuyama, Seishi; Nakamichi, Haruo; Yamada, Katsumi; Endo, Shigeru (ISIJ International, 2013)
Based on the strain-based concept of linepipe products, materials with high deformability are desirable and a dual-phase microstructure consisting of harder and softer phases is essential to obtain higher deformability. Martensite-austenite constituents (MA) are very important in the hard phase for achieving good mechanical properties such as deformability and toughness. For understanding the formation process and its effect on mechanical properties, microstructural analysis of the MA formed through two different heat treatments (on-line heat process and off-line heat process) is conducted. Based on SEM and TEM observation, it is found that the MA consisted mainly of martensite and its distributions and shapes are different between on-line and off-line heat process samples. Because of the different formation processes, grain boundary character is also different. The interface of MA and matrix in the on-line heat process sample is divided by short length Kurdjumov-Sacks (K-S) orientation grain boundaries. On the other hand, long length random grain boundaries are formed at the interface of the off-line heat process material. This characteristic morphology results in the difference in the toughness of the materials by causing a different strain accumulation and crack propagations mechanism at the vicinity of MA.